A Critical Interpretation on Mutraghata (Retention of Urine) - A Review Study - Bandhe, Ashok Kumar; Nirmalkar, Uttam Kumar; Singh, Balendra; Normal, Satrupa (International Research Journal of Ayurveda & Yoga, 2021)
There are many patients suffering from various kinds of Mutra Vaha Srotas disorders. Information such as Nidana, Samprapti, Lakshanas, Sadhya- Asadhyata, Upadrava, Chikitsa should be known to any physician. Due to retention or relative anuria or oliguria, Mutraghata has been identified by Acharya Dalhana to be a Mutra vaha Srotas clinical body, where urine flux is obstructed. Obstructed urine (Mutraghata) is diseased while it is holding Cardinal characteristic is urine. Hence urinary retention may be caused by urinary tract occlusion or urinary pathway inflammation. This influences can also be used as the nidana of Mutraghata for dushti of Mutra vaha Srotas. Because of this cause, the doshas get worse. It’s vata dosha mainly. The vitiated dosha mixes with urine and thus prevents the urine flow.